Fluorescent half-sandwich phosphine-sulfonate iridium(III) and ruthenium(II) complexes as potential lysosome-targeted anticancer agents. (March 2019) - Du, Qing; Yang, Yuliang; Guo, Lihua; Tian, Meng; Ge, Xingxing; Tian, Zhenzhen; Zhao, Liping; Xu, Zhishan; Li, Juanjuan; Liu, Zhe
Abstract: The synthesis, characterization and biological activity of neutral fluorescent Ir(III) and Ru(II) half-sandwich organometallic complexes containing phosphine-sulfonate ligands are reported. X-ray crystal structure of complexes1 –3, 10 and11 exhibits the expected half-sandwich "three-legged piano-stool" pseudo-octahedral geometry. Spectroscopic properties study displays that these complexes show rich fluorescence properties. With the exception of9, 10 and11 toward A549 human lung cancer cells and10 towards HeLa human cervical cancer cells, each complex shows promising cytotoxicity toward HeLa and A549 cells line with IC50 values in the range of 3.6–53.1 μM, and 6.5–34.5 μM, respectively. Hydrolysis, DNA cleavage and depolarization of the mitochondrial membrane potential (MMP) appear not to be the main mechanism of action. However, these complexes are able to covert NADH to NAD + via the transfer hydrogenation. Mechanism studies by flow cytometry display that the complexes exert their anticancer efficacy by inducing apoptosis, perturbing the cell cycle and increasing the intracellular ROS level. Furthermore, fluorescence property of these complexes provides a tool to investigate the microscopic mechanism by confocal microscopy. Notably, the typical Ir(III) complex3 can specially localize to lysosome and damage it. In addition, complex3 enters into HeLa cells mainly through energy-dependent pathway. Graphical abstract: A series of fluorescent phosphine-sulfonate iridium(III) and ruthenium(II) half-sandwich complexes have been synthesized and characterized. Most of these complexes display promising anticancer activities toward HeLa and A549 cancer cells. The mechanism of actions (MoAs) of these complexes was explored by flow cytometry and confocal microscopy imaging. Highlights: Fluorescent phosphine-sulfonate Ir(III) and Ru(II) complexes have been synthesized. These complexes display promising anticancer activities. The mechanism of actions was determined by confocal microscopy.